Proteomic analysis of carbapenem-resistant Klebsiella pneumoniae outer membrane vesicles under the action of phages combined with tigecycline - Jing Mao; Xiaoyu Yang; Cheng Yan; Fan Wang; Rui Zheng (BMC, 2024)
Abstract Background Klebsiella pneumoniae is the most commonly encountered pathogen in clinical practice. Widespread use of broad-spectrum antibiotics has led to the current global dissemination of carbapenem-resistant K. pneumoniae, which poses a significant threat to antibacterial treatment efficacy and public health. Outer membrane vesicles (OMVs) have been identified as carriers capable of facilitating the transfer of virulence and resistance genes. However, the role of OMVs in carbapenem-resistant K. pneumoniae under external pressures such as antibiotic and phage treatments remains unclear. Methods To isolate and purify OMVs under the pressure of phages and tigecycline, we subjected K. pneumoniae 0692 harboring plasmid-mediated bla NDM-1 and bla KPC-2 genes to density gradient separation. The double-layer plate method was used to isolate MJ1, which efficiently lysed K. pneumoniae 0692 cells. Transmission electron microscopy (TEM) was used to characterize the isolated phages and extract OMV groups for relevant morphological identification. Determination of protein content of each OMV group was conducted through bicinchoninic acid assay (BCA) and proteomic analysis. Results K. pneumoniae 0692 released OMVs in response to different environmental stimuli, which were characterized through TEM as having the typical structure and particle size of OMVs. Phage or tigecycline treatment alone resulted in a slight increase in the mean protein concentration of OMVs secreted by K. pneumoniae 0692 compared to that in the untreated group. However, when phage treatment was combined with tigecycline, there was a significant reduction in the average protein concentration of OMVs compared to tigecycline treatment alone. Proteomics showed that OMVs encapsulated numerous functional proteins and that under different external stresses of phages and tigecycline, the proteins carried by K. pneumoniae 0692-derived OMVs were significantly upregulated or downregulated compared with those in the untreated group. Conclusions This study confirmed the ability of OMVs to carry abundant proteins and highlighted the important role of OMV-associated proteins in bacterial responses to phages and tigecycline, representing an important advancement in microbial resistance research.